A Kinetic Study of Induced Catalysed Oxidation of Alcohols by Chlorite Ions in Acidic Medium - Tiwari, Vivek; Solanki, S.K. (Asian Journal of Chemistry, 2010)
The kinetics of catalysed oxidation of iso-propanol and n-propanol by chlorite ion in acidic medium has been carried out. The catalyst (Fe2+ + Cu2+) shows predominant accelerating effect on reaction velocity. The reaction follows first and zero order with respect to oxidant and substrate concentration respectively. The reaction rate is directly proportional to the catalyst concentration. Different kinetic and activation parameters have been computed. A probable reaction mechanism has been proposed.